A proposal of ethical competence model for cyber security organization - Nor Hapiza Mohd Ariffin; Ruhaila Maskat (Institute of Advanced Engineering and Science, 2021)
A proactive cyber security plan to safeguard confidential information and privacy still lacks initiatives to avoid frequent harmful attacks. Cybersecurity professionals must possess ethical competence and prove worthy of overseeing valuable information for efficient decision‐making since ethical competence is fundamental for daily practice. There is a need to define what it means to be ethically competent in the era of IR4.0. The previous competence models still lack consideration of both artificial intelligence (AI) and emotional intelligence (EI) skills. AI brings new opportunities to cyber security organizations that focus on AI skills related to cognitive Intelligence or intelligent quotient (IQ). EI, which refers to emotional quotient (EQ), is a good predictor of ethical competence as it can perceive and express emotions precisely to facilitate thought to understand and manage emotions. However, practically, most cyber security organizations focused on AI skills and disregarded EI skills' roles. This research proposes a cyber artemotional model that blends AI skills and EI skills for cyber security employees. This research would benefit cyber security organizations with cyber artemotional model as employees ethical competence assessment, and it is in line with the demand of IR4.0.